The pedagogical side of entrepreneurship theory - Fiet, James O. (Journal of Business Venturing, 2001)
This is the second article in a set of two in this issue that deals with challenges in entrepreneurship education related to theory building and pedagogy. The first article argued that educators must increase the theoretical content in their courses if they hope to develop in students the cognitive skills to make better entrepreneurial decisions. This second article discusses a strategy for teaching entrepreneurship theory. The difficulty with teaching theory to entrepreneurship students is that they are likely to complain that “theory is boring! Lectures are boring! School is boring!” All three of these—theory, lecture, and school can also be irrelevant. We as teachers can also be boring and irrelevant! Students may not understand that learning theory can be highly interesting. Unfortunately, the process used to teach theory could be boring. We become boring as teachers when our classroom style becomes predictable because students are never surprised. We become irrelevant as teachers when we fail to apply theory as a tool to answer student questions. Good theory can always pass the test of applicability. If we fail to teach our students how to apply it in surprising ways, it is we who are at fault, not the theory. An effective strategy for teaching theory to students must be approved by them and monitored by teachers to be effective. If our purpose is to assist students to become skilled in theory-based competencies, the most effective method is to establish a student-approved system for class meetings that requires students to practice specific skills. Obtaining student approval is important because almost any system will work better if students feel good about it. In other words, students acquire competencies through their practice with theory-based activities. A theory-based activity approach is based on the assumption that to the extent that a teacher is the initiator of knowledge transfer, students tend to practice less and acquire fewer competencies. This occurs because it is the teacher who is the most engaged, not the students, which is the reverse of what is optimal. One way to evaluate our involvement in the classroom is to ask ourselves if our goal is to have students leaving class talking about how great we are as a teacher, rather than about how wonderful it would be to be an entrepreneur. If our students leave talking about being entrepreneurs instead of about us, we have probably figured out how to involve them in activities that help them to develop personal competencies. The teacher's primary role is to achieve student approval of the learning contract and to identify the theory-based competencies to be mastered. The question for educators faced with ensuring student mastery is not, “What an I going to teach today?” but “What am I going to have my students do today?” The teacher's task can be made easier by delegating part of the responsibility for the second question to students. Delegation of learning activities to students can introduce more variety and surprises into the classroom, each of which can aleviate boredom. It also provides teachers an opportunity to work more closely with students as they attempt to understand theory in anticipation of their classroom assignment to lead the learning activity. The remainder of this article discusses how to implement a theory-based activity approach, obstacles to its success and advantages of its use. The greatest advantage of its use is that students will be learning theory that can improve their odds of being successful as entrepreneurs. Of course their success depends upon us as scholars having gone before them and discovered the rules (theory) according to which events occur (c.f., Whitehead, 1917).